ANALISIS KEMAMPUAN MENDONGENG SISWA KELAS 5 SDN PANNARA KOTA MAKASSAR - Andi Khaerul; Azis Azis; Asis Nojeng (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the storytelling abilities of fifth-grade students at Pannara Elementary School, Makassar City. This study uses a descriptive approach with quantitative research methods. The population in this study were all fifth-grade students of Pannara Elementary School, Makassar City, totaling 31 students. The sampling technique used was total sampling, so that the entire population was used as the research sample. The data analysis technique used was descriptive statistics to describe students' storytelling abilities. The results of the study showed that overall students' storytelling abilities were in the capable category. Most students were included in the capable to very capable category. In the story mastery indicator, students were able to understand the content, plot, and message of the story coherently and clearly. In the intonation indicator, students were able to regulate the tone of voice, stress, and tempo of speech. The expression indicator showed students' ability to use facial expressions, body language, and gestures to support the delivery of the story. Meanwhile, in the self-confidence indicator, students were generally able to appear calm, steady, and convincing.